Pengaruh Kepercayaan, Citra Merek, Kualitas Produk, Pelayanan Dan Resiko Terhadap Minat Beli Produk Fashion Di Shopee ( Studi Pada Konsumen Dinoyo Yang Pernah Berbelanja Online Di Shopee ) - Juniarti Juniarti; Rois Arifin; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This Study Aims To Determine And Analyze The Relationship Between Trust, Brand Image, Product Quality, Service And Risk On Buying Interest In Fashion Products At Shopee. This Research Uses A Study Method On Consumers Of Dinoyo Malang City Where Data Is Obtained By Distributing Questionnaires To Consumers Of Dinoyo Malang City Which Are Selected By Purposive Sampling. Determination Of The Number Of Samples Using The Maholtra Formula And The Results Obtained Were 105 Respondents. The Analytical Method Used In This Research Is Instrument Test (Validity Test, Reliability), Normality Test, Classical Assumption Test (Multicollinearity Test, Heteroscedasticity Test), Multiple Linear Regression Analysis, Hypothesis Test (F Test And T Test), Determination Coefficient Test Processing The Data Using SPSS. The Results Of This Study Indicate That Trust, Brand Image, Product Quality, Service, And Risk Simultaneously Affect Buying Interest. Buying Interest, Service Partially Affects Buying Interest, Risk Partially Affects Buying Interest. Keywords: Trust, Brand Image, Quality, Service, Risk, Buying Interest